KEANEKERAGAMAN NGENGAT DI WANA WISATA GONOHARJO, LIMBANGAN, KENDAL, JAWA TENGAH - Nanang Kamaludin; Mochamad Hadi; Rully Rahadian (Jurnal Akademika Biologi, 2013)
Moths is insect in Order Lepidoptera of Nocturnal habit. Moths help to polinate the flower were blossom in the night. The relationship of moths and plants can be used as bio-indicators of environmental changes in the Gonoharjo forest habitats. The objective of this study are to compare the abundance and diversity of members of moth (Lepidoptera) in various habitats and to determine the status of rare and endemic species that are found in Wana Wisata Gonoharjo. This study used light traps method for moth in four different habitats, i.e., secondary forests, riparian area and forests of pine forest and coffee plantation. The research was conducted over two months during October-November 2012. The analysis used were relative abundance, diversity index, Huctheson test, evennes index and similarity index. Threety nine moth species from 10 families were found in 4 habitats of Wana Wisata Gonoharjo. The highest number of moth species found in secondary forest (30 species) and the lowest one found in the pine forests (6 species). Statistically, there were differences within the types of habitat diversity. Evennes indices in all habitats of Wana Wisata Gonoharjo were relatively high. In general, type of habitat affects species diversity of moths. Keyword : Diversity, moth and Gonoharjo forest.